Breeding and production of Acheta Domesticus as a protein source for the fish farming sector in the department of Huila applying IoT techniques - Bahamon Bahamon, Vanesa; Castro Flórez, Víctor Iván; Ordierez Zuñiga, Laura Daniela; González, Andrés Enrique (I+ T+ C- Research, Technology and Science, 2020)
The research is focused on the fish farming sector, for which the development of a low-cost IoT-controlled habitat is presented, for the breeding of insects of the Acheta domesticus species, with the aim of providing an alternative to replace commercial concentrate such as flours. and granules processed by a natural one, improving the nutritional factor of the fish, providing about 60% of proteins from a natural source. For the construction of the container, four variables that directly affect the development of the species were taken into account: luminosity, hydration, humidity and temperature; which were controlled by means of a PCB board attached to the habitat container. As a result, a modular habitat was obtained, 80% controlled by electronic equipment and sensors, allowing a low mortality rate to be guaranteed in the growth process of this species.